Enhancing water productivity and farm income through location-specific technologies: An FFP success story from tribal Odisha - Satapathy, B. S.; Mishra, S. K.; Sahu, Prativa; Sahoo, Isha Anindita; Mohanty, S.; Sethi, D.; Dash, H. K.; Jena, R. K.; Pradhan, F. K. (Indian Farming, 2025)
The ICAR-Indian Institute of Water Management implemented the Farmer FIRST Programme in the tribal-dominated cluster of Haridamada, Jamujhari, and Barapita villages in Khordha district, Odisha, to enhance water productivity and farm income in rice-based cropping systems under a canal command. Location-specific, multi-thematic interventions such as cove crop, natural resource, horticulture, livestock, and enterprise-based modules improved yield, resource-use efficiency, and livelihood resilience. Demonstrations of high-yielding, ecology-specific rice varieties, balanced nutrient management, need-based pest control, and efficient water management raised grain yield by 10–20% and increased benefit-cost ratios. Diversification into vegetables, fishery, dairy, and mushroom cultivation generated additional income and employment. Model farmers like Shri Manas Kumar Das successfully integrated multiple enterprises, achieving annual incomes above `5 lakh. The project’s participatory approach and science-led interventions demonstrated a replicable model for transforming smallholder subsistence farming into sustainable, profitable, andclimate-resilient agriculture.